Умножение частоты в гибридной электронно-волновой системе с длительным взаимодействием (двумерная модель) - Одаренко, Е. Н.; Шматько, А. А. (Сумський державний університет, 2007)
The multidimensional model of the hybrid multistage frequency multiplier on the basis of resonance and nonresonance O-type millimeter waves devices with prolonged interaction has been considered. The nonlinear self-consistent theory is used for theoretical investigation of the frequency multiplication. Multidimensional phenomena such as electron beam high-frequency layering, transversal beam-wave interaction etc are taken into account. Nonlinear effects are taken into account on all stages of the frequency multiplier interaction space. It allows to consider physical processes in the hybrid beam-wave system for arbitrary level of the input rf power.
Keywords: гибридные приборы О-типа; многомерная нелинейная теория; умножение частоты; миллиметровый диапазон